Research on multi-user access mechanism based on end-point information hopping and spreading hybrid technology - ZHANG Zuoming; LI Fangxiao; LUO Shenghan; SHI Leyi (Dianxin kexue)
As network attacks become increasingly frequent, traditional network defense technologies can no longer meet current demands. Active defense, relying on its dynamic and random characteristics, has become one of the effective methods to counter network attacks. The end-point information hopping and spreading hybrid technology is a type of active defense that, based on dynamically and randomly changing end-point information, allows the system to maintain communication even when ports are closed, thus providing excellent concealment and security. However, it has limitations in terms of transmission rate and user capacity, supporting only one-to-one communication. To address these issues, a new network communication strategy was proposed, which combined the end-point information hopping and spreading hybrid technology with sparse code multiple access (SCMA) to enhance the number of system-accessible users and overall transmission rate. Theoretical analysis and experimental results show that the system's user capacity and transmission rate have been improved while ensuring good concealment and security.